2014
DOI: 10.1016/j.jpsychores.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Turning the pink cloud grey: Dampening of positive affect predicts postpartum depressive symptoms

Abstract: Abstract:Background. Maladaptive response styles to negative affect have been shown to be associated with prospective (postpartum) depression. Whether maladaptive styles to positive affect are also critically involved is understudied, even though anhedonia (i.e. low positive affectivity) is a cardinal symptom of depression. The present study is the first to investigate the predictive value of cognitive response styles to both negative (depressive rumination) and positive affect (dampening) for postpartum depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
1
28
2
Order By: Relevance
“…This is the first study to provide numerical evidence to support qualitative research (Bailey et al, 2004;Cloherty et al, 2004;Lee, 2007;Mozingo et al, 2000;Earle, 2000;Cairney et al, 2006) and quantify the highly pervasive nature of negative emotions occurring among formula-feeding women. Moreover, they are a precursor to more serious postnatal mood disorders and potentially deleterious maternal or infant health outcomes (Raes et al, 2014;Glasheen, Richardson, & Fabio, 2010;Grace, Evindar, & Stewart, 2003). These findings indicate a widespread public health issue that requires urgent attention from infant feeding policy makers in order to protect the emotional wellbeing of formula feeding mothers at an already precarious time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to provide numerical evidence to support qualitative research (Bailey et al, 2004;Cloherty et al, 2004;Lee, 2007;Mozingo et al, 2000;Earle, 2000;Cairney et al, 2006) and quantify the highly pervasive nature of negative emotions occurring among formula-feeding women. Moreover, they are a precursor to more serious postnatal mood disorders and potentially deleterious maternal or infant health outcomes (Raes et al, 2014;Glasheen, Richardson, & Fabio, 2010;Grace, Evindar, & Stewart, 2003). These findings indicate a widespread public health issue that requires urgent attention from infant feeding policy makers in order to protect the emotional wellbeing of formula feeding mothers at an already precarious time.…”
Section: Discussionmentioning
confidence: 99%
“…Mood disturbances are more common postpartum as compared to prepartum or the rate that characterizes women in the general population (O'Hara et al, 2012;Viguera et al, 2011;Wenzel et al, 2005). Moreover, they are a precursor to more serious postnatal mood disorders and potentially deleterious maternal or infant health outcomes (Raes et al, 2014;Glasheen, Richardson, & Fabio, 2010;Grace, Evindar, & Stewart, 2003). Undesirable emotions relating to infant feeding may exacerbate these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barnum et al [25] found that levels of rumination (brooding) predicted increases in depression symptoms from the third trimester to 8 weeks (but not 4 weeks) post-partum. Raes et al [26] reported that rumination did not predict levels of post-partum depression at 12 or 24 weeks when baseline depression and history of depression were controlled. In other studies, a more complex picture has emerged – suggesting that rumination is predictive of depression (in pregnant women at high risk of becoming depressed) but only in combination with other factors (e.g., social functioning [27]).…”
Section: Potential Roles Of Rnt In the Perinatal Contextmentioning
confidence: 99%
“…Several studies using the RPA in nonclinical samples found that positive affect regulation strategies are related to depression scores above and beyond brooding, concurrently (Raes et al, 2009) as well as prospectively (Raes et al, 2012(Raes et al, , 2014. Although it has been suggested that strategies to regulate positive emotions are likely involved in recovery from loss (Folkman, 2001;Stroebe and Schut, 2001), to the best of our knowledge, this notion has never been empirically tested.…”
mentioning
confidence: 98%